Rhamnose-Positive Strains of Plague Agent: Virulence and Epidemiological Significance - A. A. Sludsky; Z. L. Devdariani (Проблемы особо опасных инфекций)
The aim of the review is to show the groundlessness of the unconditional assessment of rhamnose-positive strains of plague pathogen as avirulent for most species of carriers and humans and having no epidemiological significance. The main carriers of rhamnose-positive strains are several species of voles and the Mongolian pika. The vast majority of experts are of the opinion that rhamnose-positive (“vole`s” and “pika`s”) strains of Yersinia pestis are avirulent or weakly virulent for many species of warm-blooded animals and humans, and therefore have no epidemiological significance. However, in a series of experiments on infecting marmots, ground squirrels, and large gerbils with rhamnose-positive strains, some of the experimental animals fell ill acutely and died from the plague. In nature, rhamnose-positive strains have been isolated from carcasses of relatively resistant red marmots. When evaluating the epidemiological significance of rhamnose-positive strains, such an important criterion as the presence or absence of effective factors and pathways of pathogen transmission in foci of the vole and pika types is omitted. Voles and pikas are not eaten; therefore, the contact route of infecting humans in these foci is impossible. The second way of transmission of the pathogen to humans – vector-borne – is difficult due to the lack of migration of vole fleas from burrows to the surface and their low efficiency as vectors. Nevertheless, cases of human infection with rhamnose-positive strains of the plague agent in the Caucasus and Mongolia give grounds to assert that at least some rhamnose-positive strains have a sufficiently high virulence and are capable of causing infectious process in humans as well. Therefore, epidemiological surveillance in the foci of plague of the vole and pika types cannot be totally abandoned. It can be conducted according to an abbreviated scheme.